2001
DOI: 10.1063/1.1370070
|View full text |Cite
|
Sign up to set email alerts
|

Reaction pathway, energy barrier, and rotational state distribution for Li (2 2PJ)+H2→LiH (X 1Σ+)+H

Abstract: By using a pump-probe technique, we have observed the nascent rotational population distribution of LiH (v=0) in the Li (2 2PJ) with a H2 reaction, which is endothermic by 1680 cm−1. The LiH (v=0) distribution yields a single rotational temperature at ∼770 K, but the population in the v=1 level is not detectable. According to the potential energy surface (PES) calculations, the insertion mechanism in (near) C2v collision geometry is favored. The Li (2 2PJ)–H2 collision is initially along the 2A′ surface in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…2,3,6-8 Bililign et al 9 conducted laser induced pump-probe far-wing scattering experiments to study the photochemical reaction Li + H 2  LiH + H. Chen et al 10 observed the nascent rotational population distribution of LiH in the atom Li plus diatom molecule H 2 reaction by using a pump-probe technique. The comprehensive chemistry of lithium in the post-recombination epoch is presented by Stancil et al 3 and the abundances of Li, Li + , Li  , LiH and LiH + were employed for calculation as a function of red-shift z for several cosmological models.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,6-8 Bililign et al 9 conducted laser induced pump-probe far-wing scattering experiments to study the photochemical reaction Li + H 2  LiH + H. Chen et al 10 observed the nascent rotational population distribution of LiH in the atom Li plus diatom molecule H 2 reaction by using a pump-probe technique. The comprehensive chemistry of lithium in the post-recombination epoch is presented by Stancil et al 3 and the abundances of Li, Li + , Li  , LiH and LiH + were employed for calculation as a function of red-shift z for several cosmological models.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of LiH in different electronic states has been studied in several works (Chen et al 2001;Chen & Lin 2003;Bililign et al 2001). Chen et al (2001) measured the nascent rotational population distribution of the LiH molecule in its ground vibrational state in the Li * + H 2 reaction. It was concluded that the Li * + H 2 reaction is dominated by an insertion mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,16,29 The radiation sources contained two tunable dye lasers, which were pumped individually by a Nd:YAG laser operating at 10 Hz with a pulse duration of 5 -8 ns. The first dye laser at wavelength was used to prepare the Na atom in the 4 2 S, 3 2 D, and 6 2 S states at / 2 = 388.5, 342.8, and 274.9 nm by twophoton absorption, using the dyes LDS 765, LDS 698, and rhodamine 575, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…8 In the endothermic reaction of Li͑2 2 P J ͒ with H 2 , Lin and coworkers obtained a single-peaked rotational population distribution of LiH͑v =0͒, which was dominated by a reaction with Li insertion into the H-H bond. 29,32 The Li͑3 2 S ,3 2 P͒ reactions do not lead to any detectable LiH product, thereby providing indirect evidence that the harpoon mechanism cannot be applied to the Li reaction. This consequence is also supported by Lee et al from a theoretical perspective.…”
Section: Introductionmentioning
confidence: 95%